LEGAL CONSEQUENCES AGAINST BUSINESS ACTORS WHO DO NOT IMPLEMENT OCCUPATIONAL HEALTH AND SAFETY STUDIED FROM POSITIVE LAW - Fadillah, Fathur Nur; Rosifany, Ony; Kamaludin (Sekolah Tinggi Ilmu Hukum Awang Long, 2025)
Work accidents caused by companies that are negligent in implementing Occupational Safety and Health (K3) can endanger workers or laborers who are carrying out their activities in the company. They can experience minor or serious injuries, permanent disabilities, and in the worst case, can result in death for workers or laborers. Development companies must not be negligent in implementing K3 protocols in their production areas and construction areas because it can cause discomfort for workers or laborers in working and the level of work accidents has the potential to be very high. In this study, a normative legal research method was used, research materials were mostly accessed from the literature, namely materials containing new or up-to-date scientific knowledge, or new understandings of known facts or ideas, in this case including books, journals, dissertations or theses, and other legal materials. The results of the research obtained were the legal consequences for perpetrators who do not implement K3 as stated in Article 35 paragraphs (2) and (3) in conjunction with. Article 186 paragraph (1) of Law Number 13 of 2003 concerning Manpower explains that companies that provide workplaces for workers or laborers are required to provide protection that includes welfare, safety and occupational health for workers/laborers from the beginning of recruitment to work placement. Legal protection for workers who experience work accidents is an important aspect of the employment system in Indonesia, as stipulated in Law Number 13 of 2003 35 paragraphs (2) and (3) jo. Article 186 paragraph (1) and concerning Manpower.